Synergism and synergic effects in polymer`s processing technology - Yu. A. Naumova (Тонкие химические технологии, 2013)
The work deals with the terms synergism and synergic systems evolution. The analysis of literatre sources in which the results of synergic effects study in polymer`s technology are presented, is carried out. Modern approaches to estimate synergic effects, identification, analysis and synergic systems forming are reviewed, and that allows scientifically-based solving the practical receipt-biilding tasks of polymer materials and their processing technological processes parameters choice.